2016
DOI: 10.1128/aac.00871-16
|View full text |Cite
|
Sign up to set email alerts
|

First Report of German Cockroaches (Blattella germanica) as Reservoirs of CTX-M-15 Extended-Spectrum-β-Lactamase- and OXA-48 Carbapenemase-Producing Enterobacteriaceae in Batna University Hospital, Algeria

Abstract: Here we report the isolation of extended-spectrum ␤-lactamase (ESBL)-and carbapenemase-producing Enterobacteriaceae from German cockroaches caught in the burn unit of Batna University Hospital in Algeria. Nine of 12 isolates harbored the bla CTX-M-15 ESBL gene. One Enterobacter cloacae isolate belonging to sequence type 528 coexpressed the bla OXA-48 , bla CTX-M-15 , and bla TEM genes. Our findings indicate that cockroaches may be one of the most dangerous reservoirs for ESBL and carbapenemase producers in hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 33 publications
(35 reference statements)
1
24
0
Order By: Relevance
“…These data, along with those of earlier studies and the more recent description of OXA-48-producing Enterobacteriaceae from companion animals and hospital cockroaches, confirm the widespread presence of OXA-48-producing Enterobacteriaceae in Algeria (29,30).…”
supporting
confidence: 65%
“…These data, along with those of earlier studies and the more recent description of OXA-48-producing Enterobacteriaceae from companion animals and hospital cockroaches, confirm the widespread presence of OXA-48-producing Enterobacteriaceae in Algeria (29,30).…”
supporting
confidence: 65%
“…The direct transfer of AmpC-, ESBL-, or carbapenemase-producing bacteria to humans via insects seems possible, but evidence is sparse [24,35]. Loucif et al showed that 9 of 12 bacterial isolates from cockroaches in an Algerian hospital harboured CTX-M-15 genes.…”
Section: Discussionmentioning
confidence: 99%
“…Loucif et al showed that 9 of 12 bacterial isolates from cockroaches in an Algerian hospital harboured CTX-M-15 genes. Of these, one expressed an OXA-48 type carbapenemase and belonged to the sequence type 528 [24]. Elsewhere, Fotedar and colleagues indicated in an experimental study that insects fed with Pseudomonas aeruginosa could excrete the bacteria even up to 114 days post-infection[35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were subjected to the bacterialsuspension preparation and preenrichment as previously described (5). Subsequently, selective enrichment was performed in a vancomycin-and ertapenem-supplemented brain heart infusion broth (BD, France) (5).…”
mentioning
confidence: 99%